Work Readiness Of University Of Riau Management S1 Students Based On Internship Experience, Self-Efficacy And Work Motivation - Abd. Rasyid Syamsuri; Rahmat Junaidi; Rafita Rafita (CV. AFDIFAL MAJU BERKAH, 2025)
The purpose of this study was to examine the effects of internship experience, self-efficacy, and job motivation on preparedness for the workforce among undergraduate management students at the University of Riau. The sampling strategy employed in this quantitative descriptive study is proportionate stratified random sampling based on the Slovin formula. 194 pupils made up the study's sample. methods for gathering data via surveys and observation. Multiple linear regression using SPSS is the analysis approach. The analytical test's findings demonstrate that: 1) Internship experience, self-efficacy and work motivation simultaneously have a positive and significant effect on the work readiness of undergraduate management students at Riau University. 2) Internship experience has a positive and significant effect on the work readiness of undergraduate management students at Riau University. 3) Self-efficacy has a positive and significant effect on the work readiness of undergraduate management students at Riau University. 4) Work motivation has a positive and significant effect on the work readiness of undergraduate management students at Riau University. The amount of contribution of its influence is 51% or 0.51.